2009
DOI: 10.1007/s00592-008-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

The risk of developing coronary artery disease or congestive heart failure, and overall mortality, in type 2 diabetic patients receiving rosiglitazone, pioglitazone, metformin, or sulfonylureas: a retrospective analysis

Abstract: Oral anti-diabetic agents have been associated with adverse cardiovascular events in type 2 diabetes (DM2). We investigated the risk of coronary artery disease (CAD), congestive heart failure (CHF), and mortality using multivariable Cox models in a retrospective cohort of 20,450 DM2 patients from our electronic health record (EHR). We observed no differences in CAD risk among the agents. Metformin was associated with a reduced risk of CHF (HR 0.76, 95% CI 0.64-0.91) and mortality (HR 0.54, 95% CI 0.46-0.64) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 21 publications
3
71
0
3
Order By: Relevance
“…Observational data regarding the rate of heart failure with the use of SUs has been mixed, with two studies (25,26) finding an association between SU treatment and an increased rate of heart failure compared with metformin treatment, and one study (27) finding no association between SU treatment and heart failure in the context of a case-control analysis compared with no SU exposure. Beyond heart failure, the increased risk of other cardiovascular events with SU therapy is better established in clinical trials (28) and observational studies (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Observational data regarding the rate of heart failure with the use of SUs has been mixed, with two studies (25,26) finding an association between SU treatment and an increased rate of heart failure compared with metformin treatment, and one study (27) finding no association between SU treatment and heart failure in the context of a case-control analysis compared with no SU exposure. Beyond heart failure, the increased risk of other cardiovascular events with SU therapy is better established in clinical trials (28) and observational studies (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the potential adverse effects attributed to some drugs [6,7], the clinical importance of physical activity, as well as that of therapeutic education [8] is even increasing. However, the terms ''physical activity'' and ''exercise'' denote two different concepts [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have found that in comparison to metformin monotherapy, sulfonylurea monotherapy increases the risk of coronary artery disease, congestive heart failure and mortality. 26,27 In the present study, metformin monotherapy was associated with a 31% (RR: 0.69) reduction in death from any cause, whereas combination therapy was associated with a 23% (RR: 0.77) reduction. The former is in agreement with the results of a recent meta-analysis of 40 randomized controlled trials, where metformin was associated with a decreased risk (OR: 0.74, 95%CI: 0.62, 0.89) of cardiovascular mortality compared to other OHAs or placebo.…”
Section: Discussionmentioning
confidence: 71%